Chromosome-scale Amaranthus tricolor genome provides insights into the evolution of the genus Amaranthus and the mechanism of betalain biosynthesis. (6th December 2022) - Wang, Hengchao; Xu, Dong; Wang, Sen; Wang, Anqi; Lei, Lihong; Jiang, Fan; Yang, Boyuan; Yuan, Lihua; Chen, Rong; Zhang, Yan; Fan, Wei
Abstract: Amaranthus tricolor is a vegetable and ornamental amaranth, with high lysine, dietary fibre and squalene content. The red cultivar of A. tricolor possesses a high concentration of betalains, which has been used as natural food colorants. Here, we constructed the genome of A. tricolor, the first reference genome for the subgenus Albersia, combining PacBio HiFi, Nanopore ultra-long and Hi–C data. The contig N50 size was 906 kb, and 99.58% of contig sequence was anchored to the 17 chromosomes, totalling 520 Mb. We annotated 27, 813 protein-coding genes with an average 1.3 kb coding sequence and 5.3 exons. We inferred that A. tricolor underwent a whole-genome duplication (WGD) and that the WGD shared by amaranths occurred in the last common ancestor of subfamily Amaranthoideae. Moreover, we comprehensively identified candidate genes in betalain biosynthesis pathway. Among them, DODAα1 and CYP76ADα1, located in one topologically associated domain (TAD) of an active (A) compartment on chromosome 16, were more highly expressed in red leaves than in green leaves, and DODAα1 might be the rate-limiting enzyme gene in betalains biosynthesis. This study presents new genome resources and enriches our understanding of amaranth evolution, betalains production, facilitating molecular breeding improvements and the understanding of C4 plants evolution.